2018
DOI: 10.1103/physrevlett.121.237203
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Néel Temperature of Hexagonal Ferrites by Structural Distortion

Abstract: To tune the magnetic properties of hexagonal ferrites, a family of magnetoelectric multiferroic materials, by atomic-scale structural engineering, we studied the effect of structural distortion on the magnetic ordering temperature (TN). Using the symmetry analysis, we show that unlike most antiferromagnetic rareearth transition-metal perovskites, a larger structural distortion leads to a higher TN in hexagonal ferrites and manganites, because the K3 structural distortion induces the three-dimensional magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…[10,13] It was proposed that strain/ stress engineering of the hexagonal films will duly change the c/a ratio in lattice, enabling to achieve T N values above 200 K. [9] Structural distortion in epitaxially grown h-ScFeO 3 films was used to increase the K 3 phonon mode amplitude, the high measured T N of the film was correlated to lattice distortion. [8,14] The work confirmed the importance of spin-lattice coupling in manipulation of ferroic properties in lattices of h-REFeO 3 , as in their counterparts the h-REMnO 3 lattices. [15] Beside of Neel ordering temperature, additional magnetic contributions below T N have been observed in both bulk and thin films of the hexagonal lattice, with origin attributed to spin reorientation.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…[10,13] It was proposed that strain/ stress engineering of the hexagonal films will duly change the c/a ratio in lattice, enabling to achieve T N values above 200 K. [9] Structural distortion in epitaxially grown h-ScFeO 3 films was used to increase the K 3 phonon mode amplitude, the high measured T N of the film was correlated to lattice distortion. [8,14] The work confirmed the importance of spin-lattice coupling in manipulation of ferroic properties in lattices of h-REFeO 3 , as in their counterparts the h-REMnO 3 lattices. [15] Beside of Neel ordering temperature, additional magnetic contributions below T N have been observed in both bulk and thin films of the hexagonal lattice, with origin attributed to spin reorientation.…”
supporting
confidence: 58%
“…[17] Values of c-axis of 11.690 or 11.710 Å were reported for thin films of ScFeO 3 deposited on ALO, where Sc has smaller ionic radii than Lu. [8,18] The films of LuFeO 3 deposited on YSZ substrates with different techniques show smaller out of plane lattice constants, 11.750, 11.700, and 11.810 Å as to be compared to the films grown on ALO substrate. [9,19] In current work, for the substrate with smaller in-plane lattice constant, ALO (4.749 Å), the present results indicate that doping of Lu with Sc results in shrinkage of the out of plane lattice constant of the Lu 0.5 Sc 0.5 FeO 3 thin film compared to the pure LuFeO 3 or ScFeO 3 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For tiny crystals with perfect quality (the mosaic is instrument-resolution-limited), all of the reflections can be snapshotted and corrected by the instrument resolution. The smallest crystal that has been measured at HB-3A is an YbFeO 3 hexagonal ferrite thin film (5 mm × 5 mm × 50 nm~0.001 mm 3 ), and the ordered Fe-moment size determined was 2 µ B [13]. The weak superlattice peaks originating from an Fe/Cu site order in a superconductor material NaCuFeAs were also collected by snapshotting Bragg peaks at HB-3A, and the refinement confirmed that it is a Fe/Cu stripe structure.…”
Section: Capability For Tiny Crystalsmentioning
confidence: 99%
“…One of the promising candidates in modern alternative energy as the basis of solid fuel elements are perovskite-like systems based on RFeO 3 ferrite (R = Ce, Y, Ba, Sr) [14,15,16,17,18]. The increased interest in this class of structures is due to their distorted crystal structure with the possibility of filling vacancies with equivalent iron ions [19], which has an essential impact on the structural, optical, magnetic, and dielectric properties [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%